The Influence of Diet and Nutrients on Platelet Function - McEwen, Bradley J. (Seminars in Thrombosis and Hemostasis, 2014)
Cardiovascular disease (CVD) is the leading cause of death worldwide. Platelet activation and aggregation play an integral role in hemostasis and thrombosis. Diets and nutrients play a potential role in modifying CVD progression, particularly in platelet function, and have the potential of altering platelet function tests. Diets such as Mediterranean diet, high in omega-3 polyunsaturated fatty acids (PUFA), and vegetarian diets have inverse relationships with CVD. Dark chocolate, foods with low glycemic index, garlic, ginger, omega-3 PUFA, onion, purple grape juice, tomato, and wine all reduce platelet aggregation. Dark chocolate and omega-3 PUFA also reduce P-selectin expression. In addition, dark chocolate reduces PAC-1 binding and platelet microparticle formation. Berries inhibit platelet function (PFA-100). Energy drinks have been shown to increase platelet aggregation and caffeine increases platelet microparticle formation. Therefore, repeat testing of platelet function may be required, not only after exclusion of known antiplatelet medications but also potentially after exclusion of dietary substances/nutrients that could have plausibly affected initial test data.
Keywords: cardiovascular disease; platelet function; nutrients; diet